Islamic Law Review on Weighing Practices in Palm Oil Trading (Study on Weighing Practices in Palm Oil Sales and Purchases in Pematang Rahim Village) - Sayuti, Ade Rahman (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2021)
Abstract: In the practice of weighing the sale and purchase of palm oil, it must be done consensual, honest, fair and open, trusting each other, avoiding elements of fraud, ambiguity and harm from one side. This attitude can be done by perfecting the measurements and scales at the time of weighing practice, in the sale and purchase of palm oil in Pematang Rahim Village, the process of weighing palm oil in determining the results of the scales is determined only by one side determined by the buyer, without going through a mutual agreement with the owner. selling palm oil. This causes a compulsion to accept the results of the weighing practice in buying and selling palm oil. So in this case there is compulsion so that the seller must accept the system that has been set by the buyer of palm oil. The thing that wants to be examined is how the practice of weighing in buying and selling palm oil in Pematang Rahim village is. Review of Islamic Law on the practice of weighing in the sale and purchase of palm oil. The method used is a qualitative method with the type of research used in this research is field research. The review of Islamic law on the practice of weighing in the sale and purchase of palm oil in Pematang Rahim contradicts the letter Al-Isra 'verse 35 because the party who benefits is the buyer of palm oil while the seller is harmed.